Penerapan Integrated Marketing Communication (IMC) dalam Meningkatkan Target Penjualan Pada Brand Toko Online Jakjek Store di Jakarta Timur - Indira Cahyarani; Sugeng Santoso (PANDITA : Interdisciplinary Journal of Public Affairs, 2022)
Integrated Marketing Communication (IMC) is the process of developing and implementing various forms of persuasive communication programs to customers and potential customers. IMC is a combination of several mix of marketing communication promotion strategies which include Advertising, Direct Marketing, Internet Marketing, Sales Promotion, Personal Selling and Public Relations. Jakjek Store began to implement the promotional strategy mix in 2019 to increase its sales target, by focusing on its online reseller business. In carrying out this strategy, Jakjek Store has a supporting factor, namely being consistent in doing online marketing, while the inhibiting factor is that the existence of the brand they bring is unstable or can go up/down. Jakjek Store favors promotional strategies in advertising and direct marketing, and also provides communicative services. Jakjek Store implements all mixes of integrated marketing communication strategies, by maximizing advertising strategies and also direct marketing in increasing sales targets. The existence of the product is an obstacle in sales because it is not stable.This study uses a qualitative method with a descriptive approach. Data collection techniques used are observation, interviews and documentation. Sources of data used are primary and secondary with the number of informants as many as 5 people. Keywords: Integrated Marketing Communication, Promotional Strategy Mix, Sales Target